Arterial hypertension in women at different ages - Pacheco-Romero, José (2010)
Hypertension is associated to co-morbidities such as diabetes mellitus, coronary artery disease, stroke, peripheral vascular disease, chronic renal failure, entities that decrease life span. Peruvians suffer from arterial hypertension with characteristics similar to those of the general population. Early detection and treatment of hypertension should benefit them with years of quality of life. The occurrence of arterial hypertension in women from childhood through menopause, including reproductive years and pregnancy, is described.